1990
DOI: 10.1063/1.345369
|View full text |Cite
|
Sign up to set email alerts
|

Formation, oxidation, electronic, and electrical properties of copper silicides

Abstract: The solid state reaction between copper and silicon has been studied using Rutherford backscattering, glancing-angle x-ray diffraction, scanning electron microscopy, and x-ray photoemission spectroscopy. Schottky-barrier-height measurements on n-type Si (100) have also been performed in the temperature range of 95–295 K with the use of a current-voltage technique. The results show that a metal-rich compound with a composition in the Cu3Si range forms at low temperatures (473 K). The electronic properties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(71 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…Strongly bonded Cu may catalyze the Si-O bond breaking, since Cu also catalyzes the reverse reactions of Si-O formation. 13,14,[16][17][18] Metal evaporation as applied by others 9,21 may result in a weaker metal-support interaction 4 and, therefore, not result in a reaction between Cu and SiO 2 during UHV annealing. We note that also impurities on the sample surface or constituents of the residual gas may help to reduce SiO 2 .…”
Section: Fig 2 Aes Results Of Amentioning
confidence: 99%
See 2 more Smart Citations
“…Strongly bonded Cu may catalyze the Si-O bond breaking, since Cu also catalyzes the reverse reactions of Si-O formation. 13,14,[16][17][18] Metal evaporation as applied by others 9,21 may result in a weaker metal-support interaction 4 and, therefore, not result in a reaction between Cu and SiO 2 during UHV annealing. We note that also impurities on the sample surface or constituents of the residual gas may help to reduce SiO 2 .…”
Section: Fig 2 Aes Results Of Amentioning
confidence: 99%
“…13,14,16 Roomtemperature oxidation of Si is catalyzed by Cu 3 Si and a thick amorphous SiO 2 layer grows spontaneously beneath the Curich layer. 17,18 So the ease of regeneration of the annealed Cu/SiO 2 samples as described above can be understood from the oxidation behavior of a silicide and is another piece of evidence for the presence of Cu silicide after annealing in UHV.…”
Section: Fig 2 Aes Results Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…5 Macroscopic studies on and models of the properties of copper silicides have also indicated a hybridization of the valence Cu and Si orbitals. 29,[57][58][59] The increased delocalization of Cu valence electrons can qualitatively explain the Cu-K absorption edge shift to higher energies: as they are photo-excited out of the atom, Cu 1s core electrons experience a greater Coulombic attraction with the Cu nucleus due to reduced electron screening, and thus require higher x-ray energies for photoionization.…”
Section: Distribution and Chemical State Of Cu-rich Clustersmentioning
confidence: 99%
“…12,13) Amongst all the face-centered cubic (fcc) materials, copper (Cu) tends to be one of the most commonly used for the coating of silicon substrates in the fabrication of modern electronic devices dues to its high chemical stability, low resistivity, good patterning ability, good reliability, ready availability, and low cost. 14,15) Various physical and chemical methods have been proposed for the fabrication of Cu/Si systems with coherent layers. [16][17][18][19] It is known that the bonding strength of the Cu/Si system is enhanced via the precipitation of copper silicide particles via a solid state reaction when the interface between the thin Cu film and the Si substrate is heated to a sufficient temperature.…”
Section: Introductionmentioning
confidence: 99%